Estimating the Drivers of Diversification of Stoneflies Through Time and the Limits of Their Fossil Record. Issue 4 (5th August 2022) - Jouault, Corentin; Nel, André; Legendre, Frédéric; Condamine, Fabien L
Abstract: Deciphering the timing of lineage diversification and extinction has greatly benefited in the last decade from methodological developments in fossil-based analyses. If these advances are increasingly used to study the past dynamics of vertebrates, other taxa such as insects remain relatively neglected. Our understanding of how insect clades waxed and waned or of the impact of major paleoenvironmental changes during their periods of diversification and extinction (mass extinction) are rarely investigated. Here, we compile and analyze the fossil record of Plecoptera (1, 742 vetted occurrences) to investigate their genus-level diversification and diversity dynamics using a Bayesian process-based model that incorporates temporal preservation biases. We found that the Permian-Triassic mass extinction has drastically impacted Plecoptera, while the Cretaceous Terrestrial Revolution corresponds with a turnover of plecopteran fauna. We also unveiled three major gaps in the plecopteran fossil record: the Carboniferous-Permian transition, the late Early Cretaceous, and the late Cenomanian to Bartonian, which will need to be further investigated. Based on the life history of extant Plecoptera, we investigate the correlations between their past dynamic and a series of biotic (Red Queen hypothesis) and abiotic (Court Jester hypothesis) factors. These analyses highlight the major role of continental fragmentation in the evolutionary history of stoneflies, which is in line with phylogeny-based biogeographic analyses showing how vicariance drove their diversification. Our study advocates analyzing the fossil record with caution, while attempting to unveil the diversification and extinction periods plus the likely triggers of these past dynamics of diversification.